The relationship between reward and turnover intention among academic staff higher learning institution at Bandar Penawar, Kota Tinggi - Ali, Suriyani (2014)
This research investigated the level of extrinsic reward and intrinsic reward among academic staff in higher learning institutions in Bandar Penawar, Kota Tinggi. The relationship between extrinsic reward and intrinsic reward on turnover intention had been identified. Next, the role of job satisfaction and work-family enrichment had also been studied in mediating the relationship between extrinsic reward and intrinsic reward on turnover intention. The research was conducted among the academic staff in higher learning institutions in Bandar Penawar, Kota Tinggi. In this study, the data analysis techniques including means, Pearson’s analysis, multiple regression analysis and hierarchical multiple regression analysis. There are four main results in this study. First, the mean score analysis was higher in the level of extrinsic reward compared to the level of intrinsic reward among the academic staff in higher learning institutions in Bandar Penawar, Kota Tinggi. Second, the Pearson’s analysis showed that there was a significant and negative relationship between extrinsic reward and turnover intention. Meanwhile, intrinsic reward also had a significant and negative relationship with turnover intention. The multiple regression analysis showed that extrinsic reward had more influence on turnover intention compared to intrinsic reward. Lastly, the hierarchical multiple regressions showed that job satisfaction mediated the relationship between both rewards and turnover intention. In addition, work-family enrichment mediated the relationship between both rewards and turnover intention